Modified hybrid-pv renewable energy systems in remote areas - Hanaa Mohamed Farghally; Faten Hosney Fahmy; Hassan Taher Dorrah; Mohamad Ahmed Hassan (Cairo : Hanaa Mohamed Farghally, 2009)
Given the increasing demand for cleaner accessible and more economical energy sources the utilization of geothermal solar and wind energies are gaining worldwide momentum in this thesis we present an optimal design of a PV/Wind hybrid system and an economical study of a geothermal heating system applied in a three buildings in a remote area in the Eastern dessert
Thesis (Ph.D.) - Cairo University - Faculty of Engineering - Department of Electrical Power and Machines
Issued also as CD
Keywords: Geothermal energy; Photovoltaic energy; Wind energy